VD_FINDINFO Jug / 2011 / 290 vom 11. August 2011 - VD Tribunal cantonal (2011)
FIXATION DE LA PEINE, SURSIS PARTIEL À L'EXÉCUTION DE LA PEINE | 123 ch. 1 CP, 139 ch. 1 CP, 140 CP, 144 al. 1 CP, 147 CP, 186 CP, 285 CP, 2 al. 1 DPMin, 25 DPMin, 36 al. 1 let. c DPMin, 19a ch. 1 LStup, 44 PPMin, 45 PPMin